CONSUMPTIVE BEHAVIOR OF STUDENTS OF KOREAN MOVIE SERIES FANS ON SOCIOLOGY STUDENTS OF FISIP RIAU UNIVERSITY - Minnatussonia "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted at the Faculty of Social and Political Sciences, Riau University, Pekanbaru City. The purpose of this study is to find out: 1. What is the level of consumptive behavior of students who are fans of Korean Movie Series. 2. What are the internal and external factors that drive the emergence of consumptive behavior. This research uses Quantitative method. Data collection techniques in this study were questionnaires and online search methods. This study used simple random sampling, where there were 84 respondents who were randomly selected using an online questionnaire. The data analysis technique in this study was descriptive quantitative using SPSS version 23. The results of the Consumptive Behavior of Korean Movie Series fans Students showed that 46 (54.76%) respondents were categorized as having a high consumptive level, and as many as 38 (45.23%) respondents were categorized as moderate. The consumptive behavior of students who are fans of Korean Movie Series is in the form of impulsiveness, extravagance, and pleasure. There are two factors that influence consumptive behavior, namely internal factors and external factors. Internal factors originating from within the respondent such as perception, knowledge, learning, the most influential internal factor is perception with a total score of 360. External factors originating from outside the respondent such as lifestyle, community, social class, and peers, external factors the most influential is social class with a total score of 340. Keyword : Consumtive Behavior, Student, Korean Movie Series